2018
DOI: 10.1002/14651858.cd012345.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acids for the primary and secondary prevention of cardiovascular disease

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 436 publications
2
41
0
4
Order By: Relevance
“…Effects on body weight and measures of adiposity are reported in full (not just in this subset of trials assessing cancer outcomes) in other reviews in this series so are noted in the Supplementary Tables, but not discussed further here. [2][3][4] We found no trials reporting any measure of quality of life as effects of increases in LCn3, ALA, omega-6 or total PUFA.…”
Section: Secondary Outcomesmentioning
confidence: 90%
“…Effects on body weight and measures of adiposity are reported in full (not just in this subset of trials assessing cancer outcomes) in other reviews in this series so are noted in the Supplementary Tables, but not discussed further here. [2][3][4] We found no trials reporting any measure of quality of life as effects of increases in LCn3, ALA, omega-6 or total PUFA.…”
Section: Secondary Outcomesmentioning
confidence: 90%
“…However, a high intake of red meat has been associated with the development of chronic diseases including colorectal cancer, coronary heart diseases, and type 2 diabetes . In a systematic review by Abdelhamid et al ., the authors concluded that ‘increasing polyunsaturated fatty acid (PUFA) intake probably slightly reduces the risk of coronary heart disease and cardiovascular disease events.’ On the other hand, high consumption of saturated fat has been linked to increased risks of cardiovascular and type 2 diabetes . In this regard, ruminant meat is often considered to be unhealthy due to the high content of saturated fat, which results from the biohydrogenation of dietary unsaturated fatty acids …”
Section: Introductionmentioning
confidence: 99%
“…On top of that, the American Heart Association revealed that replacing saturated fat with polyunsaturated vegetable oil can reduce CV events by 30% . Nevertheless, due to the small number of prospective trials, there is an ongoing debate over the practical utility of such dietary regimen in patients with CVD …”
Section: Introductionmentioning
confidence: 99%